2014
DOI: 10.5137/1019-5149.jtn.8514-13.4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levetiracetam on midline closure in early chicken embryos

Abstract: AIm: Genetic predisposition and some environmental factors play an important role in the development of neural tube defects. Levetiracetam is a new drug that has been approved in the treatment of partial seizures. We aimed in this study to determine the effect of levetiracetam on chick embryos. mAterIAl and methOds: One hundred and sixty fertile non-pathogenic Super Nick eggs were incubated for 24 hours and were divided into four groups of 40 eggs each. Levetiracetam was administered via the sub-blastodermic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…However, the fact that the known teratogenic agents manifest this teratogenic effect of varying levels suggests that these agents either affect the folic acid mechanism at varying levels are also affected different biochemical paths. Similar studies done previously also have shown that levetiracetam causes NTD [16,17]. In the experimental study conducted by Ozer et al on chick embryos, it was shown that levetiracetam led to midline defects and a reduction in cell proliferation [16].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the fact that the known teratogenic agents manifest this teratogenic effect of varying levels suggests that these agents either affect the folic acid mechanism at varying levels are also affected different biochemical paths. Similar studies done previously also have shown that levetiracetam causes NTD [16,17]. In the experimental study conducted by Ozer et al on chick embryos, it was shown that levetiracetam led to midline defects and a reduction in cell proliferation [16].…”
Section: Discussionsupporting
confidence: 71%
“…In the experimental study conducted by Ozer et al on chick embryos, it was shown that levetiracetam led to midline defects and a reduction in cell proliferation [16]. Ozgural et al reported that the concentration of calcium ions were affected and NTD prevalence increased depending on the dosage; and emphasized that genetic and developmental factors also needed to be considered alongside teratogenic effects [17]. The same effects were found to appear via the Fibroblast Growth Factor-2 in a study conducted by Duransoy et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to AEDs during a critical period in nervous system development causes long-term detrimental effects on the neural development (Kim et al., 2007). Various AEDs were found to induce neural tube defects in different animal models (Özer et al., 2012; Ozgural et al., 2015). The strongest evidence for drugs causing neural tube defects exists for valproic acid and carbamazepine (Mitchell et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies on early chicken embryo models, such as the effects of magnetic resonance imaging and cell phone use during pregnancy (9,21); however, too many studies have been performed with drugs. The drugs studied are antiepilectics, such as valproic acid, levetiracetam, lacosamide; analgesics, such as meloxicam, flurbiprofen, metamizole; folic acid antagonists, such as methotrexate; and myeline protector proteins such as glatiramer (3,6,7,13,15,16,18,20,22). One of the most common features of these studies is that they were conducted on early chicken embryo models.…”
Section: █ Discussionmentioning
confidence: 99%